2010
DOI: 10.1021/es102498a
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis of Life Cycle Greenhouse Gas Emissions from Petroleum-Based Fuels and Impacts on Low Carbon Fuel Policies

Abstract: The climate change impacts of U.S. petroleum-based fuels consumption have contributed to the development of legislation supporting the introduction of low carbon alternatives, such as biofuels. However, the potential greenhouse gas (GHG) emissions reductions estimated for these policies using life cycle assessment methods are predominantly based on deterministic approaches that do not account for any uncertainty in outcomes. This may lead to unreliable and expensive decision making. In this study, the uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 22 publications
3
46
0
Order By: Relevance
“…From the results of the different case studies, more information was gained for decision making using the HDS approach compared to the DQI. The confidence level which is the important factor for decision making was observed, and it can be seen that the DQI approach gave more conservative results, consistent with conclusions in Venkatesh et al [34], Tan et al [21] and Lloyd and Ries [16], which could lead to unreliable decisions. For example, the results for all the case studies showed the pure DQI approach giving a 50 % probability making any decisions made using the pure DQI quite unreliable.…”
Section: Fig 5 A-h Results Of Tio 2 and Tio 3 Wind Turbinessupporting
confidence: 85%
“…From the results of the different case studies, more information was gained for decision making using the HDS approach compared to the DQI. The confidence level which is the important factor for decision making was observed, and it can be seen that the DQI approach gave more conservative results, consistent with conclusions in Venkatesh et al [34], Tan et al [21] and Lloyd and Ries [16], which could lead to unreliable decisions. For example, the results for all the case studies showed the pure DQI approach giving a 50 % probability making any decisions made using the pure DQI quite unreliable.…”
Section: Fig 5 A-h Results Of Tio 2 and Tio 3 Wind Turbinessupporting
confidence: 85%
“…at the upper bounds. A similar observation has been made in other research works as well, where the semi-quantitative DQI approach overestimated the uncertainty [29,48,49]. In particular, the shape parameter and range endpoint appearing in the beta distribution may not be universally applicable; therefore, the beta distribution parameters (shape parameter and range endpoint) should be determined for the agricultural LCI dataset in the IDEA.…”
Section: Modification Of the Semi-quantitative Dqi Approach For The Asupporting
confidence: 77%
“…The alternative approach B solves the apparent underestimation of the uncertainty estimated by the conventional semi-quantitative DQI approaches by other researchers [29,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Through testing, we determined that 5,000 MC trials were sufficient to characterize the distributions of GHG emissions and freshwater consumption associated with the life cycle of Bakken crude, as well as individual life cycle phases. Emissions associated with combustion of gasoline and diesel were considered constant in these simulations; the coefficient of variation for these emissions has been reported to be 2% (46). Direct refinery GHG emissions per barrel of crude were also considered to be constant.…”
Section: Methodsmentioning
confidence: 99%
“…Additional data and figures of pertinence to the assessment of impacts associated with casings (54), cement, corrosion and scale inhibitors, hydraulic fracturing additives, artificial lift (operation of the pumping unit), fugitives (40), tank recirculation pumps (55), tank vapors (56), class II disposal of produced water, flaring due to infrastructural constraints (46), and crude transportation modes (13) and distances are provided in SI Appendix, section 4.1. XTO Energy uses the same service providers used by other oil and gas companies for drilling, hydraulic fracturing, and other upstream operations that directly generate GHG emissions.…”
Section: Methodsmentioning
confidence: 99%